Regards - Riva, Alessandro; Artiscope, Bruxelles (Brussel : Artiscope Bruxelles, 2004)
Basilè, Matteo ; Beckman, Ford ; Borofsky, Jonathan ; Brown, James ; Chia, Sandro ; Corneli, Fabrizio ; de Filippi, Leonida ; Depero, Fortunato ; Glaser, Milton ; Kastelic, Ronald Victor ; Licitra, Salvatore ; Ling Jian ; Man Ray ; Paolini, Giulio ; Rensonnet, Pierre-Philippe ; Rivers, Larry ; Roig, Bernardi ; Schmidlin, Paolo ; Vaccari, Wainer
Korte biog. per kunstenaar 2 p.
Publication on the occasion of the exhibition 'Regards' at the Artiscope in Bruxelles, 26.03.2004-26.06.2004
boek